Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Let [tex]$A=\left[\begin{array}{rr}-5 & 1 \\ 4 & 0\end{array}\right]$[/tex] and [tex]$B=\left[\begin{array}{rr}-1 & -2 \\ 6 & 6\end{array}\right]$[/tex].

Find [tex][tex]$B-A$[/tex][/tex], if possible.

Select the correct choice below and, if necessary, fill in the answer box to complete your choice:

A. [tex]$B - A =$ \begin{bmatrix} \square & \square \\ \square & \square \end{bmatrix}[/tex]
(Type an integer or simplified fraction for each matrix element.)

B. [tex]$B-A$[/tex] is undefined.


Sagot :

To find the matrix [tex]\( B - A \)[/tex], we need to perform subtraction of the corresponding elements from matrix [tex]\( A \)[/tex] and matrix [tex]\( B \)[/tex].

Given matrices:
[tex]\[ A = \begin{pmatrix} -5 & 1 \\ 4 & 0 \end{pmatrix} \][/tex]
[tex]\[ B = \begin{pmatrix} -1 & -2 \\ 6 & 6 \end{pmatrix} \][/tex]

The subtraction [tex]\( B - A \)[/tex] is performed element-wise as follows:

For the first element in the first row and first column:
[tex]\[ -1 - (-5) = -1 + 5 = 4 \][/tex]

For the second element in the first row and second column:
[tex]\[ -2 - 1 = -2 - 1 = -3 \][/tex]

For the first element in the second row and first column:
[tex]\[ 6 - 4 = 2 \][/tex]

For the second element in the second row and second column:
[tex]\[ 6 - 0 = 6 \][/tex]

Putting it all together, we get:
[tex]\[ B - A = \begin{pmatrix} 4 & -3 \\ 2 & 6 \end{pmatrix} \][/tex]

So the correct choice is:
A. [tex]\( B - A = \begin{pmatrix} 4 & -3 \\ 2 & 6 \end{pmatrix} \)[/tex]